The Effectiveness of a Strategy Based on Connectivism Theory in Developing Cognitive Motivation among Female Students of the Institute of Fine Arts in the Subject of Aesthetic Education (Journal of the College of Basic Education, 2026)
The present study aims to develop a strategy based on connectivism theory and examine its effectiveness in enhancing cognitive motivation among female students at the Institute of Fine Arts in Aesthetic Education. The study arises from rapid digital transformations, prompting reconsideration of traditional teaching methods and adoption of contemporary learning theories, including connectivism, which emphasizes interaction and linking multiple knowledge sources within networked environments. The researcher employed an experimental method with a partial control design, involving two equivalent groups (experimental and control) and pre- and post-tests. The sample consisted of 60 female students, equally distributed between the two groups. The experimental group received instruction via the connectivism-based strategy, while the control group followed the conventional method. The experiment lasted eight weeks. A cognitive motivation scale was administered before and after the experimentResults indicated statistically significant improvements the experimental group’s post-test scores, demonstrating the strategy’s effectiveness in developing cognitive motivation The study recommended that instructors adopt modern teaching strategies, including this strategy, in teaching the subject of aesthetic education.